2011
DOI: 10.3109/01480545.2010.532501
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal developmental toxicity study of ethyltertiary-butyl ether in rabbits

Abstract: Ethyl tertiary-butyl ether (ETBE) is commonly used as an oxygenated gasoline additive. In this study, the prenatal developmental toxicity of ETBE was determined in rabbits. New Zealand white rabbits were given ETBE by gavage at 100, 300, or 1,000 mg/kg/day on gestational days (GDs) 6-27, and the pregnancy outcome was determined on GD 28. Neither death nor abortion occurred in the pregnant rabbits at any dose. Slightly and significantly suppressed maternal body-weight gain and transiently decreased maternal foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…It is possible that higher concentrations of MTBE could result in effects on craniofacial development, although based on the morphological observations reported in Bonventre et al (2011), MTBE did not induce cranial structures deformities in treatments as high as 25 mM MTBE (Bonventre et al, 2011). Similarly, craniofacial abnormalities, including cleft palate, were previously reported for mammalian developmental models with MTBE and TAME exposure, but not with ETBE (Bevan et al, 1997, Welsh et al, 2003; Asano et al., 2011). The craniofacial structures measured in our study are similar to cleft palate formation in mammals in that they involve comparable molecular mechanisms, specifically the involvement of both WNTs and MMPs.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…It is possible that higher concentrations of MTBE could result in effects on craniofacial development, although based on the morphological observations reported in Bonventre et al (2011), MTBE did not induce cranial structures deformities in treatments as high as 25 mM MTBE (Bonventre et al, 2011). Similarly, craniofacial abnormalities, including cleft palate, were previously reported for mammalian developmental models with MTBE and TAME exposure, but not with ETBE (Bevan et al, 1997, Welsh et al, 2003; Asano et al., 2011). The craniofacial structures measured in our study are similar to cleft palate formation in mammals in that they involve comparable molecular mechanisms, specifically the involvement of both WNTs and MMPs.…”
Section: Discussionsupporting
confidence: 59%
“…Developmental inhalation studies for ETBE have not been published. However, rat and rabbit developmental studies report no adverse effects to fetuses exposed prenatally up to 1,000 mg/kg/day (9.8 moles/kg/day) ETBE (Asano et al, 2011, reviewed in de Peyster, 2010). TAME gestational inhalation studies reported NOAELs to be 1500 ppm (14.7 moles/m 3 air) for rat fetuses and 250 ppm (2.5 moles/m 3 air) for mice fetuses (Welsh et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Rabbit are the most frequently used animals in a variety of biomedical research fields. The latter fields include: neuroscience, oncology, cardiovascular, dermatology, reproduction and embryonic development [1][2][3]. Embryonic, fetal, and postnatal developmental phases of lungs are the foremost phases.…”
Section: Introductionmentioning
confidence: 99%
“…The rabbit is an excellent model used in a variety of biomedical research fields including neuroscience, oncology, embryonic development, cardiovascular studies, dermatology, and reproduction (Ewuola & Equnike, 2010; Asano et al, 2011 andGuo et al, 2012). Rabbit is an attractive species for making gonad studies due to easily identification of the morphological changes of the seminiferous epithelium cycle (Ewuola and Equnike, 2010).…”
Section: Introductionmentioning
confidence: 99%